Information Technology Infrastructure Library Framework Implementation Using Machine Learning Method - Kusuma, Muhammad Romadhona; Shidiq, Muchamad Bachram; Sudrajat, Agung (Yayasan Mitra Peduli Indonesia, 2024)
A business company must be able to adapt to the rapid development of information technology. An organization's success depends on its users' ability and desire to use technology in business activities. If a company can provide technology but fails to achieve the expected results, this can be caused by less than optimal use of technology. This study aims to discuss the importance of ITIL implementation in maintaining and constantly monitoring technology in running business processes in the company. In addition, implementation evaluation can be assessed by looking at performance in handling IT problems based on historical data on the ticketing system application. It can be analyzed using machine learning methods to obtain the best analysis results for evaluation and input for future improvement of PT Wansya Indotama Jaya.